Antimicrobial activity of some medicinal plant extracts against Gram positive and Gram negative bacteria in Bangladesh - Rahman, Md Mizanur; Shahriar, Md Raquib; Meghla, Nigar Sultana; Ishika, Tasneema; Roy, Pravas Chandra; Kamruzzaman, Md (Asian Journal of Medical and Biological Research, 2018)
Antibacterial active compounds isolated from higher plants appear to be one of the most important alternative approaches to contain antibiotic resistance and the management of disease. The present study was aimed at to investigate the antibacterial activity of some medicinal plant species including seeds namely Centella asiatica, Oxalis corniculata, Phoenix dactylifera, Clitoria ternatea and Nigella sativa. The methanolic and ethanolic extract of Centella asiatica, Oxalis corniculata, Phoenix dactylifera and Clitoria ternatea was investigated for antimicrobial activity at different concentrations by using disc diffusion method against some bacterial strains with standard antibiotic cephachlore (10 μg). The result demonstrated that all the extracts showed antibacterial activities against the isolates, which were dose dependent. The ethanolic extract of Oxalis corniculata at a concentration of 50 μl/disc had the highest effect on the test organism B. subtilis, Salmonella typhi and E. coli with 9.3, 9.7 and 10.8 mm diameter of zone of inhibition respectively while at the same concentration the extract of Clitoria ternatea had a higher antimicrobial activity on Bacillus cereus with 11.3 mm diameter of zone of inhibition. The activities of the plant extracts on the tested pathogens were not as effective as the standard commercial antibacterial disc but was significant. In case of Nigella sativa, Pseudomonas aeruginosa was sensitive to both the ethanolic extract and oils at different concentration. Salmonella typhi shows the same degree of inhibition for ethanolic extract as Bacillus cereus, but greater inhibition for oils. Of all the bacteria, Pseudomonas aeruginosa was the most sensitive bacteria against ethanolic extract and oils, while Bacillus cereus was the most resistant bacteria. Generally, the oils of Nigella sativa sample had higher antibacterial activity against bacteria than ethanolic extract. All the extracts are inhibitory to most common human pathogen S. typhi. The results suggest that the different plant extracts has a significant scope to develop a novel broad spectrum of antibacterial herbal formulations. Asian J. Med. Biol. Res. December 2017, 3(4): 405-411